Pengaruh Jadwal Sandar dan Keberangkatan Kapal terhadap Kualitas Pelayanan Kapal - Taufik MR; Nina Mutmainah; Adrian kristanto Tamara (Institut Transportasi dan Logistik Trisakti, 2019)
Reality check, there is always a late ship berthing activities or not docking on time at the port. There are several reasons caused this which leads to the low quality of ship’s services. This research was conducted at PT. Pertamina Trans Kontinental Balikpapan Branch with quantitative research method and multiple linear regression analysis test equipment. The t test and F test were used to test the significance. . Based on the results of the study,there is a significant effect between ship docking schedule on service quality, and the relationship of both positive with r value = 0.657 (strong). There is a significant influence between ship departure to service quality and the relationship between the two is positive with a value of r = 0.716 (strong). There is a significant effect between joint berthtime and departure schedules on service quality, with a value of r = 0.75 in the category of strong relationships. The regression equation is Ŷ = 1.161 + 0.359X1 + 0.624X2.